PEREMPUAN,PEMANASAN GLOBAL,DAN PELESTARIAN LINGKUNGAN - Nur, Suriani (PSW, 2010)
: The womanâs participation has related to the quality of environmental. If the woman is active, the environment will be clean, green, regular, and respect, On the contrary if the environment is damage, the most suffering are woman and children. The woman role that relates to the environment activities, are for example domestic or residence,Â workplace, agriculture environment, and more relevant places.The woman role cannot be denied in giving a good contribution to improve and or lessen the global warming, because culture patriarkhi which still stick in this part of society. That, the woman reside in domestic region, manage children and all their need, manage hygiene, also the woman are as bursar going shopping and so on, in everyday requirement accomplishment. So that environmental arrangement in smallest structure from global world namely family reside in on-hand woman, it is included in environtmental friendlyproduct election reside must be in on-hand of them.